Effects of Combined Physical Activity and Cognitive Training on Cognitive Function in Older Adults with Subjective Cognitive Decline: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (29th April 2021) - Sun, Qianqian; Xu, Shurui; Guo, Shuai; You, Yue; Xia, Rui; Liu, Jiao
Abstract : Background . Subjective cognitive decline (SCD) is recognized as the earliest prodromal stage of Alzheimer's disease (AD). Emerging studies explored the effects of combined physical activity and cognitive training interventions on cognitive ability, psychological well-being, and emotion of older adults with SCD, but the results are now still controversial. Objective . This study systematically evaluated the enhancement effects of the combined physical-cognitive interventions on memory self-efficacy, objective cognitive function, psychological well-being, and emotion of older adults with SCD. Methods . Data sources PubMed, EMBASE, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang degree and conference papers database, Chinese Science and Technology Periodical (VIP) databases from their inception to 28 February 2020, the Cochrane Central Register of Controlled Trials (Cochrane Library, 2020, Issue 3), and the reference lists of all retrieved articles were searched. Data analysis and bias risk evaluation were conducted in 2020. Two reviewers (SG and YY) independently evaluated the risk of bias of the included studies using the RoB 2 tool. Results . Eleven RCTs involving 1713 participants with SCD (age 68.0 ± 6.1) were included for review and meta-analysis. The interventions in the included studies were physical activity combined with cognitive training. Multiple-modality exercise with mind-motor training, supervised strategy-based memory training sequentially after stationary cycling, Dejian Mind-Body intervention, and physical activity and cognitive stimulation were also practiced. Conclusions . Compared to the active or nonactive control groups, the combined interventions are effective in improving objective cognitive function in SCD which may show the potential value of combined physical-cognitive interventions in improving objective cognitive ability and preventing the conversion of SCD to MCI or AD and no adverse effects. However, owing to the limitations of the included studies, these findings should be interpreted cautiously.